The Mechanism of Land Rights Transfer in the Case of Name Discrepancies Between Administrative Documents and Land Ownership Certificates - Ompusunggu, Novia Fransisca; Mudiparwanto, Wahyu Adi (LEGAL BRIEF, 2025)
Land ownership represents a fundamental aspect of agrarian law in Indonesia, yet discrepancies between names listed in administrative documents and land certificates create significant legal uncertainties that can undermine property rights and generate disputes. This research aims to identify the mechanism for transferring land rights when such discrepancies occur and to assess the legal status of the land ownership in these cases. The study employed a normative legal method with a statute approach, analyzing primary legal materials including Law No. 5 of 1960 (UUPA), Government Regulation No. 24 of 1997, and related regulations, supported by secondary sources. The findings show that the settlement process involves coordination among government agencies, starting from problem identification at the sub-district level, clarification at the Population and Civil Registration Office (Dukcapil), and resolution at the National Land Agency (BPN). Name discrepancies caused by typographical or administrative errors do not affect the validity of ownership, whereas discrepancies due to unregistered transfers result in legal uncertainty and potential disputes. The study concludes that ensuring clarity in land certificates is crucial to achieving legal certainty, preventing disputes, and protecting certificate holders, highlighting the importance of mandatory registration of all transfers within 30 days.